Surface modifications of oil palm mesocarp fiber by superheated steam, alkali, and superheated steam-alkali for biocomposite applications - Then, Yoon Yee; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Ariffin, Hidayah; Wan Yunus, Wan Md. Zin; Chieng, Buong Woei (North Carolina State University, 2014)
In this work, surface modifications of oil palm mesocarp fiber were carried out by using superheated steam, alkali, and consecutive superheated steam-alkali treatments, aiming at modification of fiber’s surface for biocomposite applications. The chemical compositions of fiber were modified after treatments as validated by chemical analysis and Fourier transform infrared spectroscopy. The treated fibers under microscopy observation showed relatively clean, rough, and textured surfaces due to the elimination of impurities and hemicellulose. The crystallinity index and thermal stability of treated fibers were relatively higher than that of untreated fiber as determined by X-ray diffraction and thermogravimetric analyses, respectively. A reduction in water absorption of fiber after treatments was also noted. These results indicated those treatments were effective in modifying the chemical compositions and microstructure of fiber. The treatments also increased the crystallinity and thermal stability, as well as reduced the hygroscopicity of fiber. Those treatments could increase the suitability of fiber to be used in the development of biocomposites.